Dotyk fortepianu. Wybrane zagadnienia fenomenologii wykonania i percepcji utworu muzycznego - Chęćka, Anna (Res Facta Nova, 2018)
The main purpose of the article is to reflect on performer’s aesthetic concretization of a musical work. The virtuoso’s concretization blurs the boundaries of the subject and the object of experience: the musician becomes a screen for music, embodies it. The artist’s perception is sharpened, which is shown in the article based on the experience of a pianist performing Claude Debussy’s music. Especially important – apart from hearing – is the sense of touch in this experience. The analysis of the experience of the perceptive performer presented here is in a significant way inspired by the pedagogical practice of the French pianist, Alfred Cortot – his statements, recordings and testimonies of his pupils. On the theoretical side, it is founded on the phenomenology of Maurice Merleau-Ponty and Michel Henry, and indirectly also refers to the comments of Roman Ingarden about aesthetic concretization.